IMPLEMENTATION OF THE EXPORT POTENTIAL OF UKRAINE’S GRAIN SECTOR IN THE CONTEXT OF GLOBAL CHALLENGES: STRATEGIC PRIORITIES AND INSTITUTIONAL MECHANISMS - TATARENKO, Nataliya; NABOK, Inna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article investigates the implementation of Ukraine’s grain export potential under global challenges and full-scale war. It substantiates Ukraine’s role as one of the leading exporters of wheat, corn and barley in ensuring food security for countries in Asia, Africa, the EU and the Middle East. The dynamics of grain production and exports in the 2019–2024 marketing years are analysed, along with structural shifts in export flows, including the growing share of corn and oilseeds and changes in the geography of supplies caused by seaport blockades, infrastructure destruction and logistical constraints. The impact of international initiatives (the Black Sea Grain Initiative, “Solidarity Lanes”, alternative Black Sea and Danube routes) on the partial stabilisation of export flows is revealed. The theoretical framework is based on institutional economics and the concept of global value chains, which makes it possible to interpret export potential as a result of the interaction between state policy, market incentives and infrastructure development. The article defines strategic priorities for strengthening export potential: infrastructure modernisation, diversification of logistics routes, development of deep grain processing and expansion of exports of value-added products, as well as enhancement of risk management tools (insurance, hedging, agricultural receipts). The authors propose key directions for institutional reforms aimed at improving the transparency and predictability of the regulatory environment, supporting agricultural producers and exporters, and intensifying international coordination. It is concluded that a comprehensive logistics, investment and regulatory policy is crucial for restoring and strengthening Ukraine’s long-term positions in the global grain market.
Keywords: world grain market; export potential; Ukrainian grain market; development